COMPARISON OF PROSTAGLANDIN E2 GEL, PROSTAGLANDIN E2 PESSARY AND EXTRA-AMNIOTIC SALINE INFUSION WITH OXYTOCIN FOR INDUCTION OF LABOUR - Qamar, Saima; Bashir, Adeela; Ibrar, Faiza (Journal of Ayub Medical College Abbottabad, 2012)
Background: Induction of labour is the intentional initiation of cervical ripening and uterine contraction for the purpose of accomplishing delivery, prior to onset of spontaneous parturition. This study was conducted to compare maternal and neonatal outcome in women induced with Prostaglandin E2 gel, Prostaglandin E2 pessary and extra-amniotic saline infusion with oxytocin at Bishops score <5. Methods: It was a quasi-experimental which was conducted at the Department of Gynaecology and Obstetrics Unit-I, Mother and Child Health Care Centre, Pakistan Institute of Medical Sciences, Islamabad during one year of time. Eighty cases in each group (prostaglandin gel, prostaglandinE2 pessary and extra-amniotic saline infusion with oxytocin) were collected. Systematic sampling was done. First woman admitted was induced with prostaglandin gel, the second one with prostaglandin pessary and the third was induced with extra amniotic saline infusion and oxytocin. Results: The most common indication for induction was post dates followed by PIH. The induction labour interval was less in EASI with oxytocin group (5.18±3.4) hours, as compared to prostaglandin pessary (8.81±5.60) hours and prostaglandin gel (8.32±5.18) hours. Induction delivery interval in EASI with oxytocin was (10±5.6) hours as compared to prostaglandin pessary (14±6.3) hours and prostaglandin gel (13±7.1) hours. This difference was statistically significant. The primigravidas had longer duration of labour than multigravidas. Induction labour interval in primigravidas was (8.2±5.1) hours while in multigravidas it was (6.7±5.02) hours. Induction delivery interval was also more in primigravidas (13.6±6.80) hours as compared to multigravidas (11.4±6.20) hours. Vaginal delivery rate was 89.2% while the caesarean section rate was 10.4%. The most common indication for caesarean section was foetal distress. There was no significant difference in perinatal morbidity and mortality in the three groups. Conclusion: EASI with oxytocin is a better method of induction than prostaglandin E2 gel and pessary. Moreover it is more economical in our country. Keywords: Induction of labour, Bishop score, EASI, Prostaglandin E2